Pengaruh Harga dan Kualitas Terhadap Minat Beli Konsumen Buket Bunga: (Studi Kasus pada Syerr Art Collections) - Eka Amelia Octaviani; Roby Setiadi; Muhammad Syaifullah (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study has the main objective, namely to find out how the influence of price and product quality on consumer buying interest in flower bouquets at Syerr Art Collections. This research uses quantitative research with the SPSS 28 for windows analysis tool. The population used in this study were consumers from Syerr Art Collections, totaling 300, with a sample of 75 respondents. The data collection method was carried out by distributing questionnaires online, namely through the Google form. The results of this study indicate that there is a positive effect of price on consumer buying interest with a significance value that is smaller than the probability value, namely 0.001 <0.05 and t count is greater than t table, namely 5.328> 1.99346. Product quality also has a positive influence on consumer buying interest with a significance value of 0.001 <0.005 and t count is greater than t table which is 4.3331> 1.99346. The two variables in this study, namely price and product quality, also jointly influence the variable of consumer buying interest with a significance value of 0.001 <0.005, and f count is greater than f table 39.445> 3.12.